2000
DOI: 10.1130/0016-7606(2000)112<1736:mmtdot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Middle Miocene tectonic development of the Transition Zone, Salta Province, northwest Argentina: Magnetic stratigraphy from the Metán Subgroup, Sierra de González

Abstract: Magnetostratigraphy, isotopic dating, and sandstone petrography establish age limits on the depositional history of ϳ2100 m of foreland basin strata in the Neogene Metán Subgroup of northwest Argentina. The strata were deposited between ca. 15.1 and 9.7 Ma in the eastern Sistema de Santa Bárbara. The region is positioned above the Cretaceous Salta rift basin, in the Transition Zone between modern relatively steep and flat subducting segments of the Nazca plate.Formations within the subgroup are shown to be dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 31 publications
5
85
1
1
Order By: Relevance
“…This is virtually identical to inverted extensional structures in the Eastern Cordillera of Colombia (e.g., Mora et al, 2006;Parra et al, 2009) and bears resemblance to the pattern of reactivated structures in the North American Laramide province (Marshak et al, 2000). Thus, the pre-Andean paleogeography of northwestern Argentina has left an imprint on the manner in which Cenozoic shortening is accommodated, resulting in a broad zone of deformation without a well-defined, tectonically active orogenic front and unsystematic lateral growth (e.g., Allmendinger et al, 1983;Grier et al, 1991;Mon and Hongn, 1991;Reynolds et al, 2000;Carrera et al, 2006;Ramos et al, 2006;Hongn et al, 2007;Hilley and Coutand, 2010). The broken foreland in Argentina therefore constitutes a morphotectonic province with spatially and temporally disparate range uplifts and intervening basins, a setting akin to the hydrologically isolated adjacent basins of the Altiplano-Puna in the orogen interior (Alonso et al, 1984(Alonso et al, , 1991Jordan and Alonso, 1987;Kraemer et al, 1999;Carrapa et al, 2005).…”
Section: Retroarc Topography Deformation and Deposition In The Centmentioning
confidence: 92%
“…This is virtually identical to inverted extensional structures in the Eastern Cordillera of Colombia (e.g., Mora et al, 2006;Parra et al, 2009) and bears resemblance to the pattern of reactivated structures in the North American Laramide province (Marshak et al, 2000). Thus, the pre-Andean paleogeography of northwestern Argentina has left an imprint on the manner in which Cenozoic shortening is accommodated, resulting in a broad zone of deformation without a well-defined, tectonically active orogenic front and unsystematic lateral growth (e.g., Allmendinger et al, 1983;Grier et al, 1991;Mon and Hongn, 1991;Reynolds et al, 2000;Carrera et al, 2006;Ramos et al, 2006;Hongn et al, 2007;Hilley and Coutand, 2010). The broken foreland in Argentina therefore constitutes a morphotectonic province with spatially and temporally disparate range uplifts and intervening basins, a setting akin to the hydrologically isolated adjacent basins of the Altiplano-Puna in the orogen interior (Alonso et al, 1984(Alonso et al, , 1991Jordan and Alonso, 1987;Kraemer et al, 1999;Carrapa et al, 2005).…”
Section: Retroarc Topography Deformation and Deposition In The Centmentioning
confidence: 92%
“…more accurate methods have been developed in the last century); (2) poor biozonation due to long ranges of the fauna; (3) diachronism at the base and top of the marine transgression, interpreted as evidence of one undifferentiated event, though Haq et al (1987) and Galloway (1989) showed that sedimentary cycles are typically repetitive with durations shorter than the interval originally interpreted for the Paranense cycle; and (4) a poor understanding of the uplift history of the central Andes. Recent work by Reynolds et al (1994Reynolds et al ( , 2000Reynolds et al ( , 2001, Hernández et al (1999Hernández et al ( , 2002, and Echavarría et al (2003) provide significant insight into the tectonic evolution of this region.…”
Section: Chronologymentioning
confidence: 94%
“…The western limit appears to have been very irregular and is poorly constrained. Western areas, where the presence of the Paranense Sea is documented, are as follows: San Juan province with the marine extension of Chinches Formation (Perez et al, 1996), Tucumán and Salta provinces east of Sierra de Aconquija (Gavriloff and Bossi, 1992a,b), the valley of Río Salí (Rio Salí Formation), and Salta and Jujuy provinces (Anta Formation, Gebhard et al, 1974;Russo and Serraioto, 1978;Galli et al, 1996;Reynolds et al, 2000).…”
Section: Middle Miocene Maximum Flooding Eventmentioning
confidence: 96%
See 1 more Smart Citation
“…3) records a transition from primary volcanic facies in a likely subaerial environment to resedimented volcaniclastic facies in a water-dominated setting. The regional context (Reynolds et al 2000;Hernandez et al 2005) constrains the setting to be continental, with the depositional environment probably ranging from shallowwater lacustrine, to swampy and alluvial.…”
Section: Discussionmentioning
confidence: 99%